EMBRACE Healthcare Reform: A Comprehensive Analysis of the Next Generation Healthcare System - Venkata Bhanuprasad Ananthavaram (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The EMBRACE (Expanding Medical and Behavioral Resources with Access to Care for Everyone) healthcare reform plan represents a comprehensive transformation of the United States healthcare system. This innovative framework integrates multiple healthcare delivery models, combining elements of universal coverage, private insurance markets, and evidence-based medicine while leveraging advanced technology infrastructure. The plan addresses critical challenges in healthcare accessibility, affordability, and quality through a multifaceted approach that includes value-based payment reform, social determinants of health integration, and enhanced digital health solutions. EMBRACE’s design emphasizes both preventive care and chronic disease management, supported by robust clinical decision support systems and telemedicine capabilities. The article incorporates community-based initiatives and environmental health programs while maintaining a focus on reducing healthcare disparities and improving outcomes across diverse populations.